2014
DOI: 10.4103/0973-1482.131353
|View full text |Cite
|
Sign up to set email alerts
|

Critical neurological structure sparing radiosurgery of vestibular schwannoma: Dosimetric comparison of different techniques and dose prescription methods

Abstract: This dosimetric data provides a guideline for choosing optimum treatment option and scope of inter institutional dosimetric comparison for further improvement in radiosurgery of Vestibular Schwannoma (VS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…They showed that VMAT using 5 coplanar arcs produced superior Paddick CI for targets larger than 0.5 cc compared to GK, but the mean cochlear dose (6.0 [1.4] Gy) was higher. Their prescription [28] created 5 different sets of static conformal field, DCAT and IMRT SRS plans for their cohort of 8 patients and, of these, the two DCAT and IMRT plans that prescribed 12 Gy to the 80% isodose line are of interest here. Unlike our study, IMRT was able to significantly lower the mean cochlear dose (5.0 [0.98] Gy), but not the maximum cochlear dose (9.8 [1.8] Gy), compared with DCAT.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that VMAT using 5 coplanar arcs produced superior Paddick CI for targets larger than 0.5 cc compared to GK, but the mean cochlear dose (6.0 [1.4] Gy) was higher. Their prescription [28] created 5 different sets of static conformal field, DCAT and IMRT SRS plans for their cohort of 8 patients and, of these, the two DCAT and IMRT plans that prescribed 12 Gy to the 80% isodose line are of interest here. Unlike our study, IMRT was able to significantly lower the mean cochlear dose (5.0 [0.98] Gy), but not the maximum cochlear dose (9.8 [1.8] Gy), compared with DCAT.…”
Section: Discussionmentioning
confidence: 99%
“…Only Andrews et al [16] found a significant difference, with a rate of hearing preservation that was 2.5 higher in the patients treated with FSRT, However, Andrews used Gammaknife radiosurgery and prescribed the treatment dose to the 50% isodose, while many other studies used LINAC SRS and prescribed the dose to the 80 to 100% isodose. This may have influenced the dose distribution to the cochlea and acoustic nerve, and, as a result, may have had an impact on hearing outcome [22]. However, he did not perform a DVH analysis.…”
Section: Discussionmentioning
confidence: 99%